Comparative cytogenetic analysis of fishes in the genus Trichopodus (Osphronemidae) in Thailand - WEERAYUTH SUPIWONG; Prayoon Wongchantra; WEERA THONGNETR; BOONYADA MINGKWAN; PATCHARAPORN CHAIYASAN; SITTHISAK PINMONGKHONKUL; KRIT PINTHONG; ALONGKLOD TANOMTONG (Society for Indonesian Biodiversity, 2021)
Abstract. Supiwong W, Wongchantra P, Thongnetr W, Mingkwan B, Chaiyasan P, Pinmongkhonkul S, Pinthong K, Tanomtong A. 2021. Comparative cytogenetic analysis of fishes in the genus Trichopodus (Osphronemidae) in Thailand. Biodiversitas 22: 3029-3036. Comparative cytogenetic study of four species of the genus Trichopodus including T. leerii, T. microlepis, T. pectoralis, and T. trichopterus from Thailand, was carried out. The specimens were collected from the Basins throughout Thailand. Chromosome preparation was directly performed from the kidney tissues. Conventional staining by Giemsa solution, Ag–NOR banding by silver nitrate solution and C-banding by NaOH solution were conducted to stain the chromosomes. Results showed that four species studied have the same diploid number and fundamental number as 46 composing of all telocentric chromosomes. Karyotypes consisting of large-medium-small sizes in T. leerii, T. microlepis, T. pectoralis and T. trichopterus were 16–28–2, 14–32–0, 20–26–0 and 10–30–6 chromosomes, respectively. The marker chromosomes which present the NOR positions are the single pair in all species but there are differences in the locations and pairs such as pairs no. 1, 7, 2 and 1, respectively. Most species except T. trichopterus, NOR sites locate at interstitial region adjacent to the centromere. T. trichopterus had the telomeric NORs. Constitutive heterochromatin blocks displayed at the centromeric/pericentromeric regions of all chromosomes in T. leerii and T. microlepis whereas in T. pectoralis and T. trichopterus, those presented at not only centromeres of several chromosome pairs, but they also were found at interstitial sites. The obtained finding, cytogenetic data has species-specific. Thus, it can be used for further study on taxonomy. Moreover, this data shows the close relationship of genetics among these species so that the application for breeding may be used in the future.